An analysis of the position of Islam and Islamic standards in the legal systems of Malaysia and Egypt - Mohammad Yosefzadeh; Mahdi Zare; Mohammad Mazhari (دانش حقوق عمومی)
The dominance of the Muslim population in Islamic countries and the institution of Islam as the central foundation of people's lives has always led to the integration of religion with the management of jurisprudence in governance. Sometimes this influence is so strong that it can even be identified in the deeper layers of the legal system. Although in countries like Malaysia and Egypt efforts have been made to consider a minimal role for religion in governance, a thorough examination of the subject will reveal the positive effects of religion in their constitutional legal systems. This research aims to answer the question of how the condition of 'belief and practical commitment to Islam' is considered in holding governmental positions in Malaysia and Egypt, given the emphasis of their constitutions on the necessity of attention to Islam. According to the hypothesis of this study, religion acts as an identity-forming element in many layers of the legal system in the constitutional frameworks of Malaysia and Egypt. However, the governance perceptions in these two countries sometimes diminish the role of religion in many areas based on the separation of religion from politics, thus the condition of 'belief and practical commitment to Islam' in holding governmental positions has not been sufficiently adhered to as one of the jurisprudential requirements. This descriptive-analytical research has produced a novel perspective on the constitutional laws of the studied countries, as these Islamic countries, despite sharing a common core of Islamic thought, exhibit significant differences in the extent of its application at the higher levels of political structure, fundamental norms, and constitutional adjudication.